2020
DOI: 10.1111/ped.14159
|View full text |Cite
|
Sign up to set email alerts
|

An efficient genetic test flow for multiple congenital anomalies and intellectual disability

Abstract: Background: Genetic testing has enabled the diagnosis of multiple congenital anomalies and/or intellectual disabilities. However, because of the phenotypic variability in these disorders, selection of an appropriate genetic test can be difficult and complex. For clinical examination, particularly in clinical facilities, a simple and standardized system is needed. Methods: We compared microarray comparative genomic hybridization and clinical exome sequencing with regard to diagnostic yield, cost, and time requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A growing number of studies suggested that transcription factors play an important role in the process of neural development, and multiple genes encoding transcription factors had been identified as risk genes for neurodevelopmental disorders. , The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, , and neurodevelopment disorders, including developmental delays, , epilepsy, , ID, , and ASD . In previous studies, we found that Pax2 +/– mice showed a high level of self-grooming behavior compared with wild-type mice .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A growing number of studies suggested that transcription factors play an important role in the process of neural development, and multiple genes encoding transcription factors had been identified as risk genes for neurodevelopmental disorders. , The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, , and neurodevelopment disorders, including developmental delays, , epilepsy, , ID, , and ASD . In previous studies, we found that Pax2 +/– mice showed a high level of self-grooming behavior compared with wild-type mice .…”
Section: Discussionmentioning
confidence: 85%
“…24,25 The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS 26−28 and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, 29,30 and neurodevelopment disorders, including developmental delays, 31,32 epilepsy, 33,34 ID, 35,36 and ASD. 36 In previous studies, we found that Pax2 +/− mice showed a high level of self-grooming behavior compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of technologies that allowed whole-genome analysis like CMA and NGS and its inclusion into medical practice has contributed to the identification of genetic causes related to CA. Association between pathogenic CNVs in patients presenting MCA and non-syndromic CA has been largely described [ 7 , 13 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ], although only a few large cohort studies have been specifically performed aiming at analyzing the whole genome by array-CGH in samples with birth defects in Latin American populations [ 93 ]. Similarly, NGS data from patients with CA from our region is still scarcely represented in most of the clinical databases worldwide or in the literature [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%